Cyclic AMP signalling controls key components of malaria parasite host cell invasion machinery - Patel, Avnish; Perrin, Abigail J.; Flynn, Helen R.; Bisson, Claudine; Withers-Martinez, Chrislaine; Treeck, Moritz; Flueck, Christian; Nicastro, Giuseppe; Martin, Stephen R.; Ramos, Andres; Gilberger, Tim W.; Snijders, Ambrosius P.; et al. (PLOS Biology, 2019)
Cyclic AMP (cAMP) is an important signalling molecule across evolution, but its role in malaria parasites is poorly understood. We have investigated the role of cAMP in asexual blood stage development of Plasmodium falciparum through conditional disruption of adenylyl cyclase beta (ACβ) and its downstream effector, cAMP-dependent protein kinase (PKA). We show that both production of cAMP and activity of PKA are critical for erythrocyte invasion, whilst key developmental steps that precede invasion still take place in the absence of cAMP-dependent signalling. We also show that another parasite protein with putative cyclic nucleotide binding sites, Plasmodium falciparum EPAC (PfEpac), does not play an essential role in blood stages. We identify and quantify numerous sites, phosphorylation of which is dependent on cAMP signalling, and we provide mechanistic insight as to how cAMP-dependent phosphorylation of the cytoplasmic domain of the essential invasion adhesin apical membrane antigen 1 (AMA1) regulates erythrocyte invasion.